Initiatives to Establish a Zero-Tolerance Sexual Violence Policy at State Islamic University - Rochimah; Mahzumi, Fikri; Naf’an, Abdul Wahab (Al-Hayat: Journal of Islamic Education, 2026)
This study seeks to establish a zero-tolerance environment for sexual violence at UIN Sunan Ampel Surabaya by enhancing internal processes based on Islamic campus principles. It addresses ongoing concerns of sexual violence and the lack of effective preventive and response procedures, highlighting the significance of gender awareness and justice for victims. This study employed a Participatory Action Research (PAR) approach, grounded in the social-ecological model, comprising four stages: planning, action, observation, and evaluation. Stakeholders across the institution contributed to policy development, education, awareness campaigns, and the formation of a Sexual Violence Prevention and Handling Task Force (Satuan Tugas Pencegahan dan Penanganan Kekerasan Seksual/Satgas PPKS). Continuous evaluation enabled improvements at each phase. The findings show that campus members' awareness of sexual violence remains low, with misunderstandings regarding its forms and consequences. The study yielded significant results through participatory action, including the formation of a gender-responsive task force, policy proposals, gender education initiatives, and a "Zero Tolerance Sexual Violence" declaration. These actions increased the institution's commitment to a safe and inclusive campus. This study was limited to a single institution and relied on leadership support and readily available infrastructure. However, its structure provides a paradigm for different Islamic higher education situations. This work presents an innovative synthesis of Islamic ethics and gender justice, utilising participatory and ecological methodologies, which results in a reproducible paradigm for reducing sexual violence in higher education.